Preparation method of composite positive electrode of lithium ion battery
By pretreating active materials, preparing uniform binder slurry and adding nanocarbon fibers, the problems of uneven composition and poor structural stability in composite positive electrodes for lithium-ion batteries are solved, and the electrochemical performance and structural stability of the electrodes are significantly improved.
Patent Information
- Application Number
- CN202310911044.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
AI Technical Summary
In the existing preparation method for lithium-ion battery composite positive electrode, the dispersion and uniformity of active materials, binders and conductive agents are difficult to ensure, resulting in uneven electrode components, affecting the consistency of electrochemical performance, and at the same time, the structure of the electrode material is stable. It has poor properties and is prone to particle aggregation, precipitation and peeling problems.
By preparing active material LIFEPO4, grinding and conductive acetylene mixing, prepare binder slurry and fully mix and dissolve through ultrasonic treatment, combine the effective surface area of nano -carbon fiber, and finally through coating, drying and roller Press the steps to prepare the electrode tablet to ensure the uniformity and structural stability of the material.
It improves the electrochemical performance and structural stability of the electrode, reduces particle aggregation and peeling off, enhances the conductivity and mechanical stability of the electrode, and extends the cycle life and long-term stability of the battery.
Smart Images

Figure CN119361604A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery electrode preparation, in particular to a method for preparing a composite positive electrode of a lithium ion battery. Background Art
[0002] Lithium-ion batteries consist of a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode is usually made of lithium-containing metal oxides (such as lithium cobalt oxide, lithium iron phosphate, etc.), and the negative electrode is made of carbon materials (such as graphite). The electrolyte is usually an organic solution that can conduct lithium ions. The separator is used to separate the positive and negative electrodes to prevent short circuits.
[0003] The preparation steps of traditional mobile phone and laptop lithium batteries are usually to prepare positive electrode materials, negative electrode materials, electrolytes and separators. The positive electrode materials usually use lithium cobalt oxide (LiCoO2) or lithium iron phosphate (LiFePO4), while the negative electrode materials often use graphite. The positive electrode materials and negative electrode materials are prepared into electrode sheets respectively. The positive electrode sheets are generally prepared by mixing positive electrode materials, conductive agents and binders, while the negative electrode sheets are prepared by mixing negative electrode materials, conductive agents and binders. The positive and negative electrode sheets are stacked together and separated by separators to form an electrode group. The electrolyte is injected into the electrode group to soak it. The electrolyte is generally composed of an organic solvent containing lithium salts, which provides a medium for ion transmission during the battery charging and discharging process. Finally, the electrode group and the electrolyte are encapsulated in a protective shell.
[0004] In traditional preparation methods, the dispersion and uniformity of active materials, binders and conductive agents are difficult to ensure, which can easily lead to uneven distribution of components in the electrode and affect the consistency of electrochemical performance. At the same time, the structural stability of the electrode material is poor, and particle aggregation, precipitation and peeling problems are prone to occur, resulting in the attenuation of electrode performance. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a composite positive electrode for a lithium-ion battery, which solves the problems in the prior art that the dispersion and uniformity of active materials, binders and conductive agents are difficult to ensure, which easily leads to uneven distribution of components in the electrode and affects the consistency of electrochemical performance. At the same time, the structural stability of the electrode material is poor, and particles are prone to aggregation, precipitation and peeling.
[0007] (II) Technical solution
[0008] To achieve the above object, the present invention is implemented by the following technical scheme: a method for preparing a composite positive electrode for a lithium ion battery, characterized in that the method comprises:
[0009] Material preparation, including active material LiFePO4LFP, carbon black nanocarbon fiber composite material, conductive agent acetylene black ACET, binder polyvinylidene fluoride PVDF, solvent N-methylpyrrolidone NMP, sealed tank, stirring tank, sampling tube, stirrer, dryer, roller press;
[0010] Pretreatment of active materials: grinding and mixing the dried LiFePO4LFP powder with the conductive agent acetylene black ACET;
[0011] Prepare a binder slurry by mixing dried polyvinylidene fluoride (PVDF) powder with N-methylpyrrolidone (NMP) solvent, and fully mix and dissolve the powder through ultrasonic treatment to form a binder slurry;
[0012] mixing active material and binder slurry, mixing the pretreated active material with the binder slurry;
[0013] Electrode sheet preparation: electrode slurry is coated on aluminum foil and dried and rolled to obtain electrode.
[0014] The present invention is further configured as follows: in the material preparation step: the preparation process of the carbon black nano-carbon fiber composite material specifically includes:
[0015] preparing phenolic resin spinning solution;
[0016] preparing phenolic resin-based carbon nanofibers;
[0017] Prepare 500ml-1000ml of hydrothermal reaction solution, dissolve cobalt nitrate hexahydrate, nickel nitrate hexahydrate, urea and carbon black in deionized water twice the mass of carbon black at a mass ratio of 0.5:0.7:0.9:1;
[0018] The prepared phenolic resin-based carbon nanofibers were immersed in a hydrochloric acid solution with a mass ratio of 0.5:1 and a concentration of 5 mol / L for 30 min, and then rinsed with ethanol and water to obtain active carbon nanofibers;
[0019] The activated carbon nanofibers are mixed with a hydrothermal reaction solution and subjected to a hydrothermal reaction at 100° C. to 250° C. for 15 min to 25 min;
[0020] Then the reacted material is calcined to obtain a carbon black nano-carbon fiber composite material;
[0021] The present invention is further configured as follows: the step of preparing the phenolic resin spinning solution specifically comprises:
[0022] Dissolve polyvinyl alcohol, phenol and sodium hydroxide in a mass ratio of 0.5:0.8:1 and add them into water to obtain a mixed solution, and stir at 90°C-95°C for 30min-45min;
[0023] Add 30%-40% formaldehyde in a mass ratio of 1:0.8 to the mixed solution, and stir continuously at 50°C-60°C for 60min-90min;
[0024] After the reaction is completed, the mixture is cooled within 5-10 minutes to obtain a phenolic resin spinning solution;
[0025] In the material preparation steps:
[0026] The active material LiFePO4LFP accounts for 60%-80% of the total mass;
[0027] Carbon black nanocarbon fiber composite materials account for 10%-20% of the total mass
[0028] The conductive agent acetylene black ACET accounts for 5%-20% of the total mass;
[0029] The binder polyvinylidene fluoride PVD accounts for 5%-15% of the total mass;
[0030] The solvent N-methylpyrrolidone NMP accounts for 10%-25% of the total mass;
[0031] The specific average particle size of the active material LiFePO4LFP is 1.0 μm;
[0032] The present invention is further configured as follows: the step of preparing phenolic resin-based carbon nanofibers specifically comprises:
[0033] The phenolic resin spinning solution is spun by an electrospinning method to obtain as-spun fibers;
[0034] The as-spun fibers are solidified and carbonized to obtain phenolic resin-based nanocarbon fibers;
[0035] The pretreatment step of the active material comprises:
[0036] Step 1, add the dried LiFePO4LFP powder and the conductive agent acetylene black ACET into the ball mill of the ball mill in a ratio of 7:3;
[0037] The ball mill adopts AM400S planetary ball mill;
[0038] Step 2, start the ball mill and grind at 150-200 rpm for 2-4 hours;
[0039] The present invention is further configured as follows: the pretreatment step of the active material further comprises:
[0040] Step 3: Check the progress of ball milling and take out samples every 30 minutes for characterization and analysis to evaluate the effect of grinding;
[0041] Step 4: Using SALD-2300 particle size analyzer to measure the size of the grinding particles;
[0042] The surface morphology of the ball-milled samples was observed using transmission electron microscopy (TEM).
[0043] X-ray diffraction (XRD) was used to analyze the crystal structure of the ball-milled samples.
[0044] Step 5, repeat step 2 to step 4 until the desired effect is achieved, stop the ball milling process, open the ball mill jar, and take out the ground mixture;
[0045] The present invention is further configured as follows: in the pretreatment step of the active material, the expected effects are specifically:
[0046] Manually evaluate the grinding effect of ball milling on the particle size, surface morphology, and crystal structure of the material, and further adjust the ball milling parameters based on the analysis results to obtain the desired material properties and particle characteristics;
[0047] The particle size in the expected effect is specifically: particle size between 6 μm and 23 μm;
[0048] There is no obvious distortion or shift in the diffraction peak, and the width of the diffraction peak is between 0.5° and 1.5°;
[0049] The present invention is further configured as follows: the step of preparing the binder slurry specifically comprises:
[0050] Step 6, preparing dry polyvinylidene fluoride PVDF powder and N-methylpyrrolidone NMP solvent;
[0051] Step 7, placing PVDF powder and NMP solvent in a sealed container in a ratio of 3:7;
[0052] Step 8, using an ultrasonic processor to ultrasonically treat the mixture for 15-20 minutes;
[0053] Step 9, sampling and observing the particle state of the mixture, with the absence of particles and lumps in the mixture as the standard;
[0054] Step 10, when the sampling does not meet the standard, repeat the ultrasonic treatment until a fully mixed and dissolved binder slurry is obtained;
[0055] Step 11: After mixing, transfer the binder slurry into a sealed bottle and store it in a sealed container to prevent volatilization and contamination;
[0056] The present invention is further configured as follows: the step of mixing the active material and the binder slurry specifically comprises:
[0057] Step 12, adding the treated active material and binder slurry into a stirring tank;
[0058] Step 13: Use a stirrer to stir the active material and binder slurry at a speed of 800-1000 rpm for 20-30 min to ensure that there are no particles and to form a uniform slurry;
[0059] Step 14: Continue stirring until the active material and the binder slurry are fully mixed to form a uniform mixture, namely, the electrode slurry.
[0060] (III) Beneficial effects
[0061] The present invention provides a method for preparing a composite positive electrode of a lithium-ion battery, which has the following beneficial effects:
[0062] The present invention grinds and mixes dried LiFePO4 (LFP) powder and conductive agent acetylene black (ACET) to increase the uniformity and contact area between the active material and the conductive agent, and improves the electrochemical performance of the electrode. At the same time, dried polyvinylidene fluoride (PVDF) powder is mixed with N-methylpyrrolidone (NMP) solvent, and fully mixed and dissolved by ultrasonic treatment to form a binder slurry, thereby improving the uniformity and dispersibility of the binder, ensuring good combination of the binder and the active material, and improving the structural stability and electrochemical performance of the electrode. The pretreated active material is then mixed with the binder slurry to ensure uniform dispersion of the two, improve the interaction between the active material and the binder, and enhance the conductivity and structural stability of the electrode. Finally, in the electrode sheet preparation process, coating, drying and rolling steps are adopted, the electrode slurry is uniformly coated on the aluminum foil by a medical scraper, and then the solvent and moisture are removed by drying. Finally, the required electrode sheet thickness is obtained by rolling, the thickness and uniformity of the electrode are controlled, and the structural stability and electrochemical performance of the electrode are improved.
[0063] At the same time, adding nanocarbon fibers increases the effective surface area of the electrode, provides more contact interfaces between the active material and the electrolyte, thereby increasing the ion transfer rate, improving the power density and charge and discharge rate performance of the battery. Adding nanocarbon fibers to the positive electrode material of the battery improves the conductivity of the overall electrode, promotes the rapid conduction of electrons, and reduces resistance loss. At the same time, the three-dimensional fiber network structure of nanocarbon fibers can enhance the mechanical stability and structural stability of the electrode, reduce the capacity attenuation and structural damage of the material, and improve the cycle life and long-term stability of the battery.
[0064] In summary, the preparation method of the lithium-ion battery composite positive electrode provided by the present invention improves the uniformity and consistency of the material, improves the performance stability and cycle life of the electrode by pretreating the active material, preparing the binder slurry and controlling the electrode sheet preparation process. By pretreating the active material, uniformly mixing the binder slurry and rolling, the structural stability of the electrode is enhanced, the aggregation and peeling of particles are reduced, and the reliability and cycle life of the electrode are improved. At the same time, it also provides a better ability to control and adjust the electrode preparation process.
[0065] The present invention solves the problems in the prior art that the dispersion and uniformity of active materials, binders and conductive agents are difficult to ensure, which easily leads to uneven distribution of components in the electrode and affects the consistency of electrochemical performance. At the same time, the structural stability of the electrode material is poor, and particles are prone to aggregation, precipitation and peeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 The present invention is a preparation flow chart of a method for preparing a composite positive electrode for a lithium-ion battery. DETAILED DESCRIPTION
[0067] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0068] Example
[0069] See also Figure 1 The present invention provides a method for preparing a composite positive electrode for a lithium ion battery, comprising the following steps:
[0070] S1. Material preparation: prepare active material LiFePO4LFP, carbon black nano-carbon fiber composite material, conductive agent acetylene black ACET, binder polyvinylidene fluoride PVDF, solvent N-methylpyrrolidone NMP, sealed tank, stirring tank, sampling tube, stirrer, dryer, roller press;
[0071] The preparation process of carbon black nanocarbon fiber composite material specifically includes:
[0072] Dissolve polyvinyl alcohol, phenol and sodium hydroxide in a mass ratio of 0.5:0.8:1 and add them into water to obtain a mixed solution, and stir at 90°C-95°C for 30min-45min;
[0073] Add 30%-40% formaldehyde in a mass ratio of 1:0.8 to the mixed solution, and stir continuously at 50°C-60°C for 60min-90min;
[0074] After the reaction is completed, the mixture is cooled within 5-10 minutes to obtain a phenolic resin spinning solution;
[0075] The phenolic resin spinning solution is spun by an electrospinning method to obtain as-spun fibers;
[0076] The as-spun fibers are solidified and carbonized to obtain phenolic resin-based nanocarbon fibers;
[0077] Prepare 500ml-1000ml of hydrothermal reaction solution, dissolve cobalt nitrate hexahydrate, nickel nitrate hexahydrate, urea and carbon black in deionized water twice the mass of carbon black at a mass ratio of 0.5:0.7:0.9:1;
[0078] The prepared phenolic resin-based carbon nanofibers were immersed in a hydrochloric acid solution with a mass ratio of 0.5:1 and a concentration of 5 mol / L for 30 min, and then rinsed with ethanol and water to obtain active carbon nanofibers;
[0079] The activated carbon nanofibers are mixed with a hydrothermal reaction solution and subjected to a hydrothermal reaction at 100° C. to 250° C. for 15 min to 25 min;
[0080] Then the reacted material is calcined to obtain a carbon black nano-carbon fiber composite material;
[0081] Among them, polyvinyl alcohol is used as the main component of the spinning solution to provide the viscosity and fluidity required for fiber formation. It is used together with PVA to form a phenolic resin-based spinning solution. Formaldehyde is used to solidify PVA and phenol in the spinning solution, adjust the acidity and alkalinity of the phenolic resin, and promote the solidification of the spinning solution. Hexahydrated cobalt nitrate and hexahydrated nickel nitrate are used for hydrothermal reaction to prepare carbon black nano-carbon fiber composite materials. Carbon black is used as a conductive additive to improve the conductive properties of the composite material.
[0082] The active material LiFePO4LFP accounts for 70%-90% of the total mass;
[0083] The conductive agent acetylene black ACET accounts for 5%-20% of the total mass and is used to improve the conductivity of the electrode;
[0084] The binder polyvinylidene fluoride PVD accounts for 5%-15% of the total mass and is used to improve the bonding force and mechanical strength of the electrode;
[0085] The solvent N-methylpyrrolidone NMP accounts for 10%-25% of the total mass;
[0086] The specific average particle size of the active material LiFePO4LFP is 1.0 μm;
[0087] S2, pretreatment of active materials, grinding and mixing the dried LiFePO4LFP powder with the conductive agent acetylene black ACET;
[0088] Step 1, add the dried LiFePO4LFP powder and the conductive agent acetylene black ACET into the ball mill of the ball mill in a ratio of 7:3;
[0089] The ball mill adopts AM400S planetary ball mill;
[0090] Step 21, start the ball mill and grind at 150-200 rpm for 2-4 hours;
[0091] Allow the ball milling media in the ball mill to fully mix and grind the LFP powder and ACET conductive agent to achieve better dispersion and combination between the LFP powder and ACET conductive agent;
[0092] Step 3: Check the progress of ball milling and take out samples every 30 minutes for characterization and analysis to evaluate the effect of grinding;
[0093] Step 4: Using SALD-2300 particle size analyzer to measure the size of the grinding particles;
[0094] The surface morphology of the ball-milled samples was observed using transmission electron microscopy (TEM).
[0095] X-ray diffraction (XRD) was used to analyze the crystal structure of the ball-milled samples.
[0096] Manually evaluate the grinding effect of ball milling on the particle size, surface morphology, and crystal structure of the material, and further adjust the ball milling parameters based on the analysis results to obtain the desired material properties and particle characteristics;
[0097] The particle size in the expected effect is specifically: particle size between 6 μm and 23 μm;
[0098] There is no obvious distortion or shift in the diffraction peak, and the width of the diffraction peak is between 0.5° and 1.5°;
[0099] Step 5, repeat step 1-1 until the desired effect is achieved, stop the ball milling process, open the ball mill jar, and take out the ground mixture;
[0100] S3, preparing a binder slurry, mixing dried polyvinylidene fluoride PVDF powder with N-methylpyrrolidone NMP solvent, and fully mixing and dissolving them by ultrasonic treatment to form a binder slurry;
[0101] The specific implementation steps are as follows:
[0102] Step 6: Prepare dry polyvinylidene fluoride (PVDF) powder and N-methylpyrrolidone (NMP) solvent.
[0103] Step 7: Place PVDF powder and NMP solvent in a sealed container at a ratio of 3:7.
[0104] Step 8: Use an ultrasonic processor to ultrasonically treat the mixture for 15-20 minutes.
[0105] Thoroughly mix and dissolve PVDF powder with NMP solvent
[0106] Step 9: Take samples to observe the particle state of the mixture, with the absence of particles and lumps in the mixture as the standard.
[0107] Step 10: If the sample does not meet the standard, repeat the ultrasonic treatment until a fully mixed and dissolved binder slurry is obtained.
[0108] Step 11: After mixing, transfer the binder slurry into a sealed bottle and store it in a sealed manner to prevent volatilization and contamination.
[0109] S4, mixing active material and binder slurry, mixing the pretreated active material with the binder slurry;
[0110] The specific mixing steps are as follows:
[0111] Step 12, adding the treated active material and binder slurry into a stirring tank;
[0112] Step 13: Use a stirrer to stir the active material and binder slurry at a speed of 800-1000 rpm for 20-30 min to ensure that there are no particles and to form a uniform slurry;
[0113] Step 14: Continue stirring until the active material and the binder slurry are fully mixed to form a uniform mixture, i.e., electrode slurry;
[0114] S5, electrode sheet preparation, coating the electrode slurry on aluminum foil and drying and rolling to obtain an electrode;
[0115] Use a medical scraper to evenly apply the electrode slurry on the surface of the aluminum foil;
[0116] The coated electrode sheet is placed in a flow dryer and dried with nitrogen gas to remove the solvent and moisture in the slurry;
[0117] The drying temperature is set to 100-150°C and the drying time is 2-4h;
[0118] The dried electrode sheet is sent into a roller press, and the electrode sheet is rolled step by step and multiple times until the thickness reaches 40-45 μm.
[0119] In view of the above, in this application:
[0120] The preparation method of the lithium ion battery composite positive electrode provided by the present invention adopts a pretreatment step of active materials, grinding and mixing dry LiFePO4 (LFP) powder with conductive agent acetylene black (ACET) to increase the uniformity and contact area between the active material and the conductive agent, and improve the electrochemical performance of the electrode.
[0121] At the same time, dry polyvinylidene fluoride (PVDF) powder is mixed with N-methylpyrrolidone (NMP) solvent, and is fully mixed and dissolved by ultrasonic treatment to form a binder slurry, thereby improving the uniformity and dispersibility of the binder, ensuring good bonding between the binder and the active material, and improving the structural stability and electrochemical performance of the electrode. The pretreated active material is then mixed with the binder slurry to ensure uniform dispersion of the two, improve the interaction between the active material and the binder, and enhance the conductivity and structural stability of the electrode;
[0122] In addition, adding nanocarbon fibers increases the effective surface area of the electrode, provides more contact interfaces between active materials and electrolytes, thereby increasing the ion transfer rate, improving the power density and charge and discharge rate performance of the battery. Adding nanocarbon fibers to the positive electrode material of the battery improves the conductivity of the overall electrode, promotes the rapid conduction of electrons, and reduces resistance loss. At the same time, the three-dimensional fiber network structure of nanocarbon fibers can enhance the mechanical stability and structural stability of the electrode, reduce the capacity attenuation and structural damage of the material, and improve the cycle life and long-term stability of the battery.
[0123] Finally, in the electrode sheet preparation process, coating, drying and rolling steps were adopted. The electrode slurry was evenly coated on the aluminum foil with a medical scraper, and then dried to remove the solvent and moisture. Finally, the required electrode sheet thickness was obtained by rolling, thereby controlling the thickness and uniformity of the electrode and improving the structural stability and electrochemical performance of the electrode.
[0124] In summary, the preparation method of the lithium-ion battery composite positive electrode provided by the present invention improves the uniformity and consistency of the material, improves the performance stability and cycle life of the electrode by pretreating the active material, preparing the binder slurry and controlling the electrode sheet preparation process. By pretreating the active material, uniformly mixing the binder slurry and rolling, the structural stability of the electrode is enhanced, the aggregation and peeling of particles are reduced, and the reliability and cycle life of the electrode are improved. At the same time, it also provides a better ability to control and adjust the electrode preparation process.
[0125] The above embodiments can be implemented in whole or in part by software, hardware, firmware or any other combination. When implemented using software, the above embodiments can be implemented in whole or in part in the form of a computer program product. The computer program product includes one or more computer instructions or computer programs. When the computer instructions or computer programs are loaded or executed on a computer, the process or function described in the embodiment of the present application is generated in whole or in part. The computer can be a general-purpose computer, a special-purpose computer, a computer network, or other programmable devices. The computer instructions can be stored in a computer-readable storage medium, or transmitted from one computer-readable storage medium to another computer-readable storage medium. For example, the computer instructions can be transmitted from one website site, computer, server or data center to another website site, computer, server or data center by wired (e.g., infrared, wireless, microwave, etc.). The computer-readable storage medium can be any available medium that a computer can access or a data storage device such as a server or data center that contains one or more available media sets. The available medium can be a magnetic medium (e.g., a floppy disk, a hard disk, a tape), an optical medium (e.g., a DVD), or a semiconductor medium. The semiconductor medium can be a solid-state hard disk.
[0126] Those of ordinary skill in the art will appreciate that the units and algorithm steps of each example described in conjunction with the embodiments disclosed herein can be implemented in electronic hardware, or a combination of computer software and electronic hardware. Whether these functions are performed in hardware or software depends on the specific application and design constraints of the technical solution. Professional and technical personnel can use different methods to implement the described functions for each specific application, but such implementation should not be considered to be beyond the scope of this application.
[0127] Those skilled in the art can clearly understand that, for the convenience and brevity of description, the specific working processes of the systems, devices and units described above can refer to the corresponding processes in the aforementioned method embodiments and will not be repeated here.
[0128] In the several embodiments provided in the present application, it should be understood that the disclosed systems, devices and methods can be implemented in other ways. For example, the device embodiments described above are only schematic. For example, the division of the units is only a logical function division. There may be other division methods in actual implementation, such as multiple units or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be through some interfaces, indirect coupling or communication connection of devices or units, which can be electrical, mechanical or other forms.
[0129] The units described as separate components may or may not be physically separated, and the components shown as units may or may not be physical units, and may be located in one place or distributed on multiple network units. Some or all of the units may be selected according to actual needs to achieve the purpose of the solution of this embodiment.
[0130] In addition, each functional unit in each embodiment of the present application may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit.
[0131] If the functions are implemented in the form of software functional units and sold or used as independent products, they can be stored in a computer-readable storage medium. Based on this understanding, the technical solution of the present application can be essentially or partly embodied in the form of a software product that contributes to the prior art. The computer software product is stored in a storage medium and includes several instructions for a computer device (which can be a personal computer, a server, or a network device, etc.) to perform all or part of the steps of the methods described in the various embodiments of the present application. The aforementioned storage media include: various media that can store program codes, such as USB flash drives, mobile hard disks, read-only memories (ROM), random access memories (RAM), magnetic disks or optical disks.
[0132] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
[0133] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite positive electrode for a lithium ion battery, characterized in that: The method includes: Material preparation, including active material LiFePO4 LFP, carbon black nanocarbon fiber composite material, conductive agent acetylene black ACET, binder polyvinylidene fluoride PVDF, solvent N-methylpyrrolidone NMP, sealed tank, stirring tank, sampling tube, stirrer, dryer, roller press; Pretreatment of active materials: grinding and mixing the dried LiFePO4 LFP powder with the conductive agent acetylene black ACET; Prepare a binder slurry by mixing dried polyvinylidene fluoride (PVDF) powder with N-methylpyrrolidone (NMP) solvent, and fully mix and dissolve the powder through ultrasonic treatment to form a binder slurry; mixing active material and binder slurry, mixing the pretreated active material with the binder slurry; Electrode sheet preparation: electrode slurry is coated on aluminum foil and dried and rolled to obtain the electrode.
2. The method for preparing a lithium-ion battery composite positive electrode according to claim 1, characterized in that: The preparation process of the carbon black nano-carbon fiber composite material specifically includes: preparing phenolic resin spinning solution; preparing phenolic resin-based carbon nanofibers; Prepare 500ml-1000ml of hydrothermal reaction solution, dissolve cobalt nitrate hexahydrate, nickel nitrate hexahydrate, urea and carbon black in deionized water twice the mass of carbon black at a mass ratio of 0.5:0.7:0.9:1; The prepared phenolic resin-based carbon nanofibers were immersed in a hydrochloric acid solution with a mass ratio of 0.5:1 and a concentration of 5 mol / L for 30 min, and then rinsed with ethanol and water to obtain active carbon nanofibers; The activated carbon nanofibers are mixed with a hydrothermal reaction solution and subjected to a hydrothermal reaction at 100° C. to 250° C. for 15 min to 25 min; Then the reacted material is calcined to obtain a carbon black nano-carbon fiber composite material.
3. The method for preparing a lithium ion battery composite positive electrode according to claim 1, characterized in that: The step of preparing the phenolic resin spinning solution specifically comprises: Dissolve polyvinyl alcohol, phenol and sodium hydroxide in a mass ratio of 0.5:0.8:1 and add them into water to obtain a mixed solution, and stir at 90°C-95°C for 30min-45min; Add 30%-40% formaldehyde at a mass ratio of 1:0.8 to the mixed solution, and stir continuously at 50℃-60℃ for 60min-90min; After the reaction is completed, the mixture is cooled within 5-10 minutes to obtain a phenolic resin spinning solution; In the material preparation steps: The active material LiFePO4 LFP accounts for 60%-80% of the total mass; Carbon black nanocarbon fiber composite materials account for 10%-20% of the total mass The conductive agent acetylene black ACET accounts for 5%-20% of the total mass; The binder polyvinylidene fluoride PVD accounts for 5%-15% of the total mass; The solvent N-methylpyrrolidone NMP accounts for 10%-25% of the total mass; The specific average particle size of the active material LiFePO4 LFP is 1.0 μm.
4. The method for preparing a composite positive electrode for a lithium ion battery according to claim 1, characterized in that: The step of preparing phenolic resin-based carbon nanofibers specifically comprises: The phenolic resin spinning solution is spun by an electrospinning method to obtain as-spun fibers; The as-spun fibers are solidified and carbonized to obtain phenolic resin-based nanocarbon fibers; The pretreatment step of the active material comprises: Step 1, add the dried LiFePO4 LFP powder and the conductive agent acetylene black ACET into the ball mill of the ball mill in a ratio of 7:3; The ball mill adopts AM400S planetary ball mill; Step 2: Start the ball mill and grind at 150-200 rpm for 2-4 hours.
5. The method for preparing a lithium ion battery composite positive electrode according to claim 1, characterized in that: The active material pretreatment step also includes: Step 3: Check the progress of ball milling and take out samples every 30 minutes for characterization and analysis to evaluate the effect of grinding; Step 4: Using SALD-2300 particle size analyzer to measure the size of the grinding particles; The surface morphology of the ball-milled samples was observed using transmission electron microscopy (TEM). X-ray diffraction (XRD) was used to analyze the crystal structure of the ball-milled samples. Step 5: Repeat steps 2 to 4 until the desired effect is achieved, then stop the ball milling process, open the ball mill jar, and take out the ground mixture.
6. The method for preparing a lithium-ion battery composite positive electrode according to claim 4, characterized in that: In the pretreatment step of the active material, the expected effects are specifically: Manually evaluate the grinding effect of ball milling on the particle size, surface morphology, and crystal structure of the material, and further adjust the ball milling parameters based on the analysis results to obtain the desired material properties and particle characteristics; The particle size in the expected effect is specifically: particle size between 6 μm and 23 μm; There is no obvious distortion or shift in the diffraction peak, and the width of the diffraction peak is between 0.5° and 1.5°.
7. The method for preparing a lithium-ion battery composite positive electrode according to claim 1, characterized in that: The step of preparing the binder slurry specifically comprises: Step 6, preparing dry polyvinylidene fluoride PVDF powder and N-methylpyrrolidone NMP solvent; Step 7, placing PVDF powder and NMP solvent in a sealed container at a ratio of 3:7; Step 8, using an ultrasonic processor to ultrasonically treat the mixture for 15-20 minutes; Step 9, sampling and observing the particle state of the mixture, with the absence of particles and lumps in the mixture as the standard; Step 10, when the sampling does not meet the standard, repeat the ultrasonic treatment until a fully mixed and dissolved binder slurry is obtained; Step 11: After mixing, transfer the binder slurry into a sealed bottle and store it in a sealed manner to prevent volatilization and contamination.
8. The method for preparing a lithium ion battery composite positive electrode according to claim 1, characterized in that: The step of mixing the active material and the binder slurry specifically comprises: Step 12, adding the treated active material and binder slurry into a stirring tank; Step 13: Use a stirrer to stir the active material and binder slurry at a speed of 800-1000 rpm for 20-30 min to ensure that there are no particles and to form a uniform slurry; Step 14: Continue stirring until the active material and the binder slurry are fully mixed to form a uniform mixture, namely, the electrode slurry.